2009
DOI: 10.1089/apc.2008.0168
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Stigma and Discrimination among Adults Living with HIV in a Low HIV-Prevalence Context: A Qualitative Analysis

Abstract: Little is known about how people living with HIV in low prevalence contexts face the challenges of stigma and discrimination. Low prevalence and rural communities are unique environments in which HIV-related stigma and discrimination may be intensified due to lower tolerance of differences among people and greater fear of HIV. This study examined the experiences of 16 individuals living with HIV who reside in a predominantly rural area with low HIV prevalence. We used in-depth interviews to explore participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 37 publications
1
78
0
1
Order By: Relevance
“…13,24,[37][38][39] Even if counseling and testing sites are close to a rural resident's home, rural residents may prefer to be tested in a different community to ensure anonymity, which can result in delayed testing. Rural providers have suggested that integrating HIV testing into other health services; rapid oral testing and community health education; outreach; and making HIV testing more convenient, accessible, and free are potential ways to decrease barriers.…”
Section: Discussionmentioning
confidence: 99%
“…13,24,[37][38][39] Even if counseling and testing sites are close to a rural resident's home, rural residents may prefer to be tested in a different community to ensure anonymity, which can result in delayed testing. Rural providers have suggested that integrating HIV testing into other health services; rapid oral testing and community health education; outreach; and making HIV testing more convenient, accessible, and free are potential ways to decrease barriers.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by findings in similar studies conducted in other African Countries which showed that people living with HIV experienced stigma and discrimination at all levels of the communities. [13][14][15][16][17] One quarter (25%) of the respondents had experienced stigmatization and discrimination (ie, unfair treatment) due to their positive HIV status. This finding is lower than findings from similar studies conducted in South Africa and Kenya, which found stigma and discrimination rates of 40% and 43%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These range from subtle to blatant and include awkward social interactions, increased physical distance, avoidance, unnecessary referrals to other health care providers, neglect, the discouragement of treatment regimens, contempt, testing without consent, blaming, excessive protective measures, the labeling of charts, beds, and/or rooms, breaches of confidentiality, refusal to treat, isolation in wards, and verbal abuse. 15,[23][24][25][26][27] Such discriminatory acts have been found to occur in hospitals, doctor's offices, dental practices, ambulances, and pharmacies. 15,[24][25][26] In fact, in a study previously conducted in the Netherlands, 26.2% of surveyed PLWH had experienced stigma in hospitals, 28.8% at their dentist's office, and 19.2% in their contact with a general practitioner.…”
mentioning
confidence: 99%
“…15,[23][24][25][26][27] Such discriminatory acts have been found to occur in hospitals, doctor's offices, dental practices, ambulances, and pharmacies. 15,[24][25][26] In fact, in a study previously conducted in the Netherlands, 26.2% of surveyed PLWH had experienced stigma in hospitals, 28.8% at their dentist's office, and 19.2% in their contact with a general practitioner. 28 In another study surveying PLWH in 14 European countries, 17% reported having experienced HIV-related discrimination from health professionals including non-HIV specialists (46%), dentists (39%), general practitioners (22%), and gynecologists (16%).…”
mentioning
confidence: 99%